Memória histórica do Massacre de Felisburgo: um estudo sobre trauma psicossocial e processos de resistência - Campos, Fabiana de Andrade (2015)
The aim of this thesis is to present the research and intervention carried out at the Terra Prometida (Promised Land) Settlement located in the Municipality of Felisburgo in the State of Minas Gerais, Brazil. In 2004, there was a massacre of the landless workers living at the settlement, which became known as The Felisburgo Massacre . It is intended to present the context of the massacre according to the Reconstruction of Historical Memory theoretical perspective while also relating it to wider context of the struggle for land in Brazil. We will discuss the subject on the basis of psycho-social studies and interventions in cases of extreme violence and relate them to the process producing affects based on the concept of ethical-political suffering coined by Sawaia. This concept seeks to analyze the political dimension of affects based on the use of this term in the work of Vygotsky and Spinoza. In order to do this, we used the work of authors who shared a socio-historical approach so that we could understand the structure/nature of the affects that constitute psycho-social trauma. The methodology is based on the premises of Socio-Historical Psychology and Liberation Psychology and the analysis of affects on Vygotskian theory. We concluded that from the workers point of view it is essential to raise the question of the massacre and share the suffering resulting from it in order to deepen both understanding of its real causes and its possible psychological consequences and to avoid it being seen as a normal phenomenon. The analysis of the data revealed the existence of mechanisms, affects and psycho-social reactions already studied by Riquelme (1993) and Martín-Baró (2000) among others, and which we have termed psycho-social trauma . In addition to this the workers were encouraged to give think carefully about the question of the seizure and occupation of land and the lack of social justice that makes them vulnerable to processes of re-traumatization. It was held that suffering and traumatization do not heal themselves or simply fade away with the passage of time. In order to break the cycle of repetition they have to be reworked. It is our opinion that Psychology can intervene in a therapeutic community by producing deep analysis with the aim of raising consciousness about the event and its consequences. The aim of the intervention was to ensure that the landless workers understood that the violent process which produced the massacre goes beyond the event itself and forms part of the historical process leading to the emergence of the Brazilian people, a process stained by innumerable forms of violence against workers. Faced with an official policy of silence, we have to develop actions to publicize the narratives, memories and diverse expressions (subjectivisations) which can be used to break through the curtain of silence and trivialization of this chain of historical violence in our country. Reversing the effects of psycho-social trauma thus means producing reflective consciousness and intensifying action